A Prospective Comparative Analysis Regarding the Assessment of Oral Mucosal Disease Using a Validated Questionnaire to Improve the Teaching of Dental Students - Röschmann, Nico; Rau, Andrea; Kesting, Marco Rainer; Maier, Eva; Buchbender, Mayte (International Journal of Environmental Research and Public Health, 2022)
Structured examination and treatment are essential in medicine. For dental students, a structured approach to the assessment of oral mucosal lesions is missing thus far. To validate an approach, a structured questionnaire was compared with the habitually used free description of oral lesions (white lesions, ulcers, hyperplasia). Thirty-three dental students were divided into two groups (Group 1 (n = 17) used the free description; Group 2 (n = 16) used a guided questionnaire) to characterize mucosal lesions in patients and make a tentative diagnosis. Although no difference was found between the groups regarding the suspected diagnosis or the histopathological findings, there was a significant advantage of the structured questionnaire in all aspects of the description compared to the free description (p = 0.000018). Thus, a structured description is an important aspect in the evaluation of oral mucosal changes, and a guided questionnaire should be implemented in the study of dentistry.
CRIS-Team WoS Importer:2022-08-26